Molecular investigation of RAD51 and DMC1 homoeologous genes of hexaploid wheat (Triticum aetivum L.) - Devisetty, Upendra Kumar (2010)
Meiotic recombination in eukaryotes requires two orthologues of the E. coli RecA proteins, Rad51 and Dmc1. Both genes play an important role in the binding of single strand DNA, homology search, strand invasion and strand exchange resulting in Holliday junctions which are resolved into crossovers or non-crossovers events. Even though both genes are well characterized in a variety of organisms including plants, very little information is available from hexaploid wheat. In most diploid plant species, deletion of either the RAD51 or DMC1 orthologues leads to sterility but wheat being a polyploid, offers a unique opportunity to examine the effects of the deletion of specific homoeologue, while maintaining a degree of fertility. The transcript expression profiling of RAD51 and DMC1 genes in Arabidopsis, rice and wheat using available microarray databases indicated higher levels of expression in mitotically and meiotically active tissues compared to other tissues. However, the possible function of the DMC1 gene in mitotic-active tissues needs to be investigated further. Previously cDNA sequences of TaRAD51 and TaDMCl of hexaploid wheat were cloned and reported. In this study, it has been demonstrated that the reported TaRAD51A1 and TaRAD51A2 cDNA sequences are (D) and (A) homoeologues of TaRAD51 respectively and TaDMCl cDNA sequence is (D) homoeologue of the TaDMC1. This study also found that the amino acid sequences and evolutionary relationships of RAD51 and DMC1 cDNA homoeologues are highly conserved across eukaryotes. Functional characterization of TaRAD51 and TaDMCl gene homoeologues was undertaken in planta using Forward Genetics, Reverse Genetics and Complementation methods. Forward and Reverse Genetic screening of a subset of a Highbury mutant population could not identify any mutants that have deletions in TaRAD51 and TaDMC1 genes. However, Reverse Genetics screening of Paragon mutant population identified mutant lines that tested as having deletions for all the three homoeologues of TaRAD51 and TaDMCl. However, most likely due to high mutational load and a deleterious phenotype, only a few mutant lines survived. Phenotypic and cytogenetic analysis indicated the probable functional redundancy of TaRAD51 (B) homoeologue in meiosis, although the unknown size of the deletion and limited phenotype makes it impossible to completely certain of this. The single mutants for TaDMC1 (B) and (D) indicated a reduction in pollen viability and ear fertility compared to wild-type. The cytological examination of these mutants indicated low levels of abnormal diakinesis, resulting in the formation of dyads. However, the single mutants were still able to produce normal tetrads. This suggests that there is a possible dosage effect of these homoeologues in hexaploid wheat. Unless deletion lines for the (A) and (D) homoeologues of TaRAD51 and (B) homoeologue of TaDMC1 can be recovered and characterized the above assumptions will remain inconclusive. The results of complementation assays using over-expressing CaMV35S::TaRAD51(D)±GFP constructs demonstrated a very low (-14% and -2%, respectively, with +GFP and -OFP constructs) functional complementation in terms of seed set compared to 0% in homozygous Atrad51 mutants. One explanation of these results is that the wheat genes are not complete functional orthologues for the inactivated Arabidopsis genes. The functional complementation experiments could not be performed for TaDMC1 gene because of time limitation, although the transformants were produced in AtDMC1/atdmc1 background. Finally, overexpression of the TaRAD51 gene suggests 2-fold increase in genetic distances in Arabidopsis using CaMV35S::TaRAD51(D) construct. This was done by crossing the appropriate transformant with fluorescent tetrad lines. However the results need to be confirmed by a large scale analysis.